Reactions in supercritical carbon dioxide - Mayadevi, S. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Use of conventional organic solvents often leads to the formation of hazardous waste, the disposal of which is a matter of environmental concern. Carbon dioxide is considered to be a green reaction medium and a good replacement for conventional organic solvents as it is benign and leads to elimination/reduction of hazardous wastes. Use of CO2 at near/above critical conditions has several additional advantages as the reactions can be pressure-tuned to eliminate transport resistance, increase solvent power and heat capacity. Hence, there has been considerable interest in the use of supercritical carbon dioxide as either a replacement of conventional organic solvent or as a co-solvent in reactions. Herein, recent developmenst in this area during the last decade is reviewed, specifically in gas-liquid (organic hydrogenation, hydroformylation and oxidation) and liquid-liquid (carbon-carbon coupling, alkylation, acetylation, esterification) reactions.
Keywords: Alkylation; Carbon dioxide; Hydroformylation; Hydrogenation; Oxidation; Supercritical carbon dioxide